IMPACT OF FLOOD ON WASTE GENERATION AND COMPOSITION IN KELANTAN - P, Agamuthu; P, Milow; A. M. N., Nurul; A. R., Nurhawa; S. H., Fauziah (Malaysian Journal of Science, 2015)
This paper presents an overview of generation and composition of waste generated from the flood that hit Malaysia from December 2014 to January 2015, particularly in Kelantan. This study recorded that during the flood event, the most abundant waste generated was wood (44%) and concrete (29%), which belong to the construction and demolition wastes category. As for waste generated within the affected area, Kuala Krai recorded the highest amount of waste during the flood which totaled 30,000 tonnes which is almost the daily generation rate in Malaysia. Values of recyclables estimated from the flood waste stream was calculated to be almost RM7 million, yet was not tapped at all due to its high contamination with other flood waste namely mud and putrescible wastes. This study concluded that flood waste generated in Kelantan is highly heterogeneous in nature but predominantly construction and demolition waste, which carried significant economic value.